Charlie Murphy the iconoclastic showman behind the Chicago Cubs - Cannon, Jason (University of Nebraska Press, 2022)
A biography of Charles Webb Murphy, the ebullient and mercurial owner of the Chicago Cubs from 1905 through 1914.